Ficus tubulosa (Moraceae), a new Amazonian species and the re-establishment of Ficus trachelosyce - Pelissari, Gisela; Neto, Sergio Romaniuc (Phytotaxa, 2014)
In this paper a new species of Ficus sect. Americana is described and illustrated as Ficus tubulosa. It is characterized mainly by the tubular shape of the ostiole, and shows morphological similarities with F. pertusa and F. trachelosyce, the latter previously treated as a synonym of F. pertusa is re-established as a valid species in this paper.